Penerapan Model CTL dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar - Yudiyanto, Yudiyanto; Nugrahani, Farida; Nurnaningsih, Nurnaningsih (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study aims to describe the implementation of the Contextual Teaching and Learning (CTL) model in Indonesian language instruction at SDN 02 Tamansari, Kerjo, Karanganyar, and to analyze teachers’ and students’ responses to its application. The research employed a descriptive qualitative approach with an embedded case study design. The main data sources consisted of teachers, students, and instructional documents, collected through observation, interviews, and document analysis. Data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the implementation of the CTL model enhances students’ active participation, strengthens their ability to compose narrative and procedural texts, and fosters a communicative and contextual learning environment. Teachers reported that the model helped them connect the material to students’ real-life experiences. This study contributes to the improvement of Indonesian language learning practices in elementary schools by emphasizing meaningful, contextual, and student-centered learning.